M6A mRNA methylation regulates testosterone synthesis through modulating autophagy in Leydig cells. Issue 2 (1st February 2021) - Chen, Yabing; Wang, Jing; Xu, Dihui; Xiang, Zou; Ding, Jie; Yang, Xiaoyu; Li, Dongmei; Han, Xiaodong
ABSTRACT: Macroautophagy/autophagy is indispensable for testosterone synthesis in Leydig cells (LCs), and here we report a negative association between m 6 A modification and autophagy in LCs during testosterone synthesis. A gradual decrease of METTL14 (methyltransferase like 14) and an increase of ALKBH5 (alkB homolog 5, RNA demethylase) were observed in LCs during their differentiation from stem LCs to adult LCs. These events led to reduced mRNA methylation levels of N 6 -methyladenosine (m 6 A) and enhanced autophagy in LCs. Similar regulation of METTL14, ALKBH5, and m 6 A was also observed in LCs upon treatment with human chorionic gonadotropin (HsCG). Mechanistically, m 6 A modification promoted translation of PPM1A (protein phosphatase 1A, magnesium dependent, alpha isoform), a negative AMP-activated protein kinase (AMPK) regulator, but decreased expression of CAMKK2 (calcium/calmodulin-dependent protein kinase kinase 2, beta), a positive AMPK regulator, by reducing its RNA stability. Thus, m 6 A modification resulted in reduced AMPK activity and subsequent autophagy inhibition. We further demonstrated that ALKBH5 upregulation by HsCG was dependent on enhanced binding of the transcriptional factor CEBPB (CCAAT/enhancer binding protein [C/EBP], beta) and the TFEB (transcription factor EB) to its gene promoter. Moreover, HsCG treatment decreased METTL14 by reducing its stability. Collectively, this study highlights a vital role of m 6 A RNA methylation in the modulation of testosterone synthesis in LCs, providing insight into novel therapeutic strategies by exploiting m 6 A RNA methylation as targets for treating azoospermatism and oligospermatism patients with reduction in serum testosterone. Abbreviations: 3-MA: 3-methyladenine; ACTB: Actin, beta; ALKBH5: alkB homolog 5, RNA demethylase; AMPK: AMP-activated protein kinase; BafA1: bafilomycin A1; CAMKK2: calcium/calmodulin-dependent protein kinase kinase 2, beta; CEBPB: CCAAT/enhancer-binding protein (C/EBP), beta; ChIP: chromatin immunoprecipitation; FTO: fat mass and obesity associated; HsCG: human chorionic gonadotropin; HSD3B: 3β-hydroxysteroid dehydrogenase; LCs: Leydig cells; m 6 A: N 6 -methyladenosine; METTL14: methyltransferase like 14; METTL3: methyltransferase like 3; MTOR: mechanistic target of rapamycin kinase; PPM1A: protein phosphatase 1A, magnesium dependent, alpha isoform; PRKAA: 5ʹ-AMP-activated protein kinase catalytic subunit alpha; SQSTM1: sequestosome 1; STK11/LKB1: serine/threonine kinase 11; TFEB: transcription factor EB; ULK1: unc-51-like kinase 1; WTAP: Wilms tumor 1-associating protein; YTHDF: YTH N6-methyladenosine RNA binding protein